Transforming Conventional Teaching Materials into Digital Visual Media: Graphic Design Training Program for MTsN Teachers - Liza Efriyanti, Liza Efriyanti; Sarwo Derta; Firdaus Annas (CV. Media Digital Publikasi Indonesia, 2026)
This Community Service Program (PKM) aimed to enhance teachers’ competencies in basic graphic design to support the development of digital learning materials at MTsN Labor Garegeh, Bukittinggi, West Sumatra. The program was motivated by the limited use of visual digital media in classroom instruction and the lack of teachers’ confidence in utilizing graphic design applications. Preliminary needs analysis indicated that more than 70% of participating teachers had never received formal training in instructional graphic design and experienced difficulties integrating visual digital media into student-centered learning activities. The activities were conducted through several stages, including needs analysis, training workshops, hands-on practice, mentoring, and evaluation. Participants were introduced to fundamental visual design principles and guided in using graphic design tools to create interactive teaching materials. The results showed a significant improvement in teachers’ understanding of graphic design concepts and their ability to produce creative digital learning resources. Teachers were able to develop visually engaging teaching materials that are more suitable for student-centered learning. In addition, participants demonstrated increased motivation to integrate technology into their instructional practices. This program contributes to strengthening teachers’ professional capacity and fostering innovation in learning. It is expected that the outcomes of this PKM will support sustainable improvements in teaching quality and encourage the wider adoption of digital media in schools.